2004
DOI: 10.1111/j.1365-2362.2004.01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral oximetry in patients with sickle cell disease

Abstract: We found that patients with sickle cell disease have subnormal values of cerebral oxygen saturation. Red cell transfusions significantly increased the brain oxygenation in these patients. Cerebral oximetry may be a useful, noninvasive method for assessing the effect of circulating normal red cells in sickle cell patients after transfusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
31
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 21 publications
9
31
2
1
Order By: Relevance
“…The result of this study is potentially important, because it helps to support the validity of the use of NIRS for detection of brain oxygenation in SCD patients, an area of considerable clinical importance. It also supports the previous reports using NIRS to measure brain oxygenation in patients with SCD patients810 and red blood cell transfusion and hydroxyurea therapy response in SCD patients 8,11,12. In our previous simple transfusion studies, we found a strong positive correlation of brain oxygen saturation with HbAA%, haematocrit and negatively with HbSS (r=0·8, p<0·001) 8.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The result of this study is potentially important, because it helps to support the validity of the use of NIRS for detection of brain oxygenation in SCD patients, an area of considerable clinical importance. It also supports the previous reports using NIRS to measure brain oxygenation in patients with SCD patients810 and red blood cell transfusion and hydroxyurea therapy response in SCD patients 8,11,12. In our previous simple transfusion studies, we found a strong positive correlation of brain oxygen saturation with HbAA%, haematocrit and negatively with HbSS (r=0·8, p<0·001) 8.…”
Section: Discussionsupporting
confidence: 92%
“…It also supports the previous reports using NIRS to measure brain oxygenation in patients with SCD patients810 and red blood cell transfusion and hydroxyurea therapy response in SCD patients 8,11,12. In our previous simple transfusion studies, we found a strong positive correlation of brain oxygen saturation with HbAA%, haematocrit and negatively with HbSS (r=0·8, p<0·001) 8. This means that lower rSO 2 values in SCD patients mainly are related to impairment of oxygen delivery and/or carrying capacity of sickle blood which contributes to tissue hypoxia and ischemia.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in support of reports that anemia in SCA patients may trigger PDGF-mediated cerebral arterial remodeling by causing disturbed and hyperemic cerebral blood flow [42], reduced cerebral oxygenation [43] and cerebral hypoxia, in addition to fluid shear stress via turbulent blood flow [44]. Cerebral hypoxia has been linked to elevated PDGF possibly via hypoxia inducible factor- 1alpha (HIF-1α) signaling [45].…”
Section: Discussionsupporting
confidence: 75%
“…In more severe subtypes hemolytic anemia is usually a persistent feature after the first months of life and creates lower blood oxygenation in the brain (Nahavandi et al, 2004). Sleep disordered breathing is more common in HbSS and may result in neurocognitive effects (Brooks et al, 1996;Hill et al, 2006;Kirkham et al, 2001a;Robertson et al, 1988;Wali et al, 2000).…”
Section: Introductionmentioning
confidence: 99%